Upaya Meningkatkan Kemampuan Bahasa Siswa Melalui Media Cerita Gambar Kelas III SD Negeri 0113 Siborong-Borong - Mhd. Rizki Ananda (Yayasan Perguruan Kampus, 2023)
The objectives in this study were (1) To determine efforts to improve student language through picture story media at SD Negeri 0113 Siborong-Borong. The research used a type of field research, the design used was PTK, namely class action research, the subject of the research the author did was at SD Negeri 0113 Siborong-Borong, Barumun Baru sub-district, Padang Lawas Regency and the object of research the author did was in class III SD Negeri 0113 Siborong-Borong which amounted to 23 students. There are two sources of data that researchers use, namely primary data sources and secondary data sources. Primary data sources are data directly taken from the object of research, namely students and third grade teachers. This primary data source comes from field data obtained from observations and interviews. Secondary data sources are data taken in the form of documents, such as books, books, dictionaries and other literature related to questioning skills. The results of the research on questioning skills showed that in the pre-cycle the students' scores were still below the KKM, namely the average student score of 59.7. Students who completed as many as 12 students with a percentage of 40.7% and students who did not complete as many as 11 students with a percentage of 59.3%. Then the questioning skills in cycle I student scores have begun to increase with an average student score of 52.8. Students who completed as many as 12 students with a percentage of 52.2% and students who did not complete as many as 11 students with a percentage of 47.8%.Then the questioning skills in cycle II student scores have increased with an average student score of 79.6.Students who completed as many as 19 students with a percentage of 86.2% and students who did not complete as many as 4 students with a percentage of 17.4%.The results showed that questioning skills in Class III of SD Negeri 0113 Siborong-Borong had improved and were well implemented.So it can be concluded that SD Negeri 0113 Siborong-Borong has implemented questioning skills well.